Правове забезпечення формування та реалізації соціальної орієнтації економіки регіонів - Вишневський, О.С. (Економіка промисловості, 2012)
Проанализировано влияние правового обеспечения стратегического планирования регионального развития на социальную ориентацию экономики регионов и определены пути совершенствования этого процесса.
Ключевые слова: социальная ориентация экономики, стратегическое планирование, законодательство, регион. Проаналізовано вплив правового забезпечення стратегічного планування регіонального розвитку на соціальну орієнтацію економіки регіонів та визначено шляхи вдосконалення цього процесу.
Ключові слова: соціальна орієнтація економіки, стратегічне планування, законодавство, регіон. The article analyzes the impact of strategic planning on the regional development of social orientation of regional economies and improvement of opportunities of this process. Poor strategic management and planning in regions of Ukraine leads to underutilization of resources and opportunities, accumulation of risks and uncertainties, and prevents the transformation of performance from the economic sphere into social one, which causes the urgency to study this issue. This situation is caused by the quality of current legislation.
The main documents that define the strategic planning process at the regional level include: Resolutions of the Cabinet of Ministers of Ukraine “On Approval of the State Regional Development Strategy for the Period until 2015”, “On Approval of the Preparation, Monitoring and Evaluation of the Regional Development Strategies”, “On Approval of the Preparation, Making and Implementation of Agreements on the Regional Development”, the draft Law of Ukraine “On the State Strategic Planning”. The analysis of these normative documents revealed the problems concerning determination of strategic goals and harmonization of estimation systems.
Therefore, the strategic planning process must be improved. It’s necessary to set measurable priorities in the regional development; improve the content of the main goals and strategic objectives in accordance with the criteria of SMART; reorient the monitoring of implementation of the State Strategy for the Regional Development to the assessment of efficiency of measures on the achievement of goals; implement a program approach in accordance with the goals (each goal must meet one program); approve an annual macroeconomic forecast made by the Cabinet of Ministers of Ukraine.
The implementation of the above recommendations can improve the quality of strategic planning, efficiency and practical realization of social orientation of the regional development.
Keywords: social orientation of economies, strategic planning, legislation, region.